Empirical Insights into Wage Dynamics and ‎MarketingCompetitiveness: A Systematic Review of India’s MSME Sector - Mohite, Rohit Ashok; Patil, Rachana; Ghunnar, Pravin; Pisal, Reshma; Vasudevan , Asokan; Akre, Sandesh (International Journal of Accounting and Economics Studies, 2025)
Purpose: This paper systematically reviews the literature on wage dynamics and marketing competitiveness within India’s Micro, Small, ‎and Medium Enterprises (MSMEs). The review identifies the interplay between labor economics, marketing orientation, and enterprise ‎competitiveness, emphasizing empirical insights into wage formation, gender pay gaps, productivity linkages, and market signaling mechanisms.‎ Design/Methodology/Approach: Following the PRISMA 2009 protocol, this systematic literature review (SLR) synthesizes 70 peer-reviewed papers from Scopus, Web of Science, and Google Scholar published between 2000 and 2025. Keywords included “wage dynamics,” “labour economics,” “marketing competitiveness,” “MSMEs,” “India,” and “labour productivity.” Only English-language empirical ‎studies on Indian MSMEs were included. Conceptual and policy-based studies were excluded.‎ Findings: The analysis indicates that marketing competitiveness significantly influences wage structures through three pathways: (1) ‎productivity-linked incentive systems, (2) labour market signaling of brand strength and firm reputation, and (3) marketing-driven product ‎diversification that enhances labour demand. However, wage rigidity persists in micro-units due to informal employment and limited financial literacy. Studies reveal wide inter-sectoral wage dispersion, gendered wage patterns, and a positive elasticity between export orientation ‎and average wages.‎ Practical Implications: This study aids policymakers and MSME managers by highlighting how marketing strategies and labor investments co-determine firm competitiveness. It further proposes integrating marketing analytics with wage-performance dashboards for equitable compensation planning.‎ Originality/Value: Few systematic reviews exist at the intersection of labour economics and marketing within MSMEs. This paper fills that ‎gap by developing a conceptual model of “Marketing-Driven Wage Competitiveness (MDWC)”, advancing theory and practice in MSME ‎labour markets‎.